Sequence analysis of Aleutian Mink Disease Virus (AMDV) isolates in captive North American mink - Vaughan, Cristina (My University, 2014)
Aleutian mink disease virus (AMDV) is a member of the parvoviridae family which primarily affects mink, often resulting in death. Nine viral genomes were amplified in segments using polymerase chain reactions (PCR) and sequenced using Sanger dideoxy method. Sequences were assembled and aligned using CLC Wo\kbench software and compared to known reference strains of AMDV. The deduced amino acid sequences were also analyzed for changes that could affect pathogenicity. Phylogenetic trees were configured for the genomic sequence as well as the all the viral proteins in order to identify strain relatedness. Phylogenetic analysis based on nucleotides revealed clustering based on ranch location, with the strains originating in Idaho and Utah clustered together and the Wisconsin strains forming a second cluster. The identification of similarities and differences between the strains can ultimately be used to help develop diagnostic tools to rapidly classify phylogenetic relationships.